Biogenic link to the recent increase in atmospheric methane over India. (1st July 2021) - Singh, A.; Kuttippurath, J.; Abbhishek, K.; Mallick, N.; Raj, S.; Chander, G.; Dixit, S.
Abstract: Methane (CH4 ) is a prominent Greenhouse Gas (GHG) and its global atmospheric concentration has increased significantly since the year 2007. Anthropogenic CH4 emissions are projected to be 9390 million metric tonnes by 2020. Here, we present the long–term changes in atmospheric methane over India and suggest possible alternatives to reduce soil emissions from paddy fields. The increase in atmospheric CH4 concentrations from 2009 to 2020 in India is significant, about 0.0765 ppm/decade. The Indo-Gangetic Plains, Peninsular India and Central India show about 0.075, 0.076 and 0.074 ppm/decade, respectively, in 2009–2020. Seasonal variations in CH4 emissions depend mostly on agricultural activities and meteorology, and contribution during the agricultural intensive period of Kharif–Rabi (i.e., June–December) is substantial in this regard. The primary reason for agricultural soil emissions is the application of chemical fertilizers to improve crop yield. However, for rice farming, soil amendments involving stable forms of carbon can reduce GHG emissions and improve soil carbon status. High crop production in pot culture experiment resulted in lower potential yield–scaled GHG emissions in rice with biochar supplement. The human impact of global warming induced by agricultural activities could be reduced by using biochar as a natural solution. Graphical abstract: Image 1 Highlights: Significant increase in methane concentration over India in last decade. Shifting trends in biogenic sources of methane is observed over India. Seasonal variation in methane concentration depends on agricultural activity. Methane emissions from soil is modulated with the application of fertilizers. Alternative organics like biochar may reduce potential soil emissions in paddy.